Peran Pemikiran Kredit Kesamaan Dari Perbankan Syariah Unit Mikro Simpan Pinjam Dan Efektifitas Kredit Dalam Meningkatkan Kesejahteraan Anggota (Studi pada Unit Simpan Pinjam Primkop Kartika Ardagusema Cimahi) - Rosmayati, Siti; Maulana, Arman (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2020)
This survey aims to identify the role and effectiveness of credit and identify the extent of the role andeffectiveness of credit undertaken by cooperatives by taking a study at Primkop Kartika ArdagusemaSavings and Credit Unit Jl. Baros No.G-151, Cimahi. To achieve this goal, many efforts are made by acooperative to achieve the achievement of prosperity, one of which is to provide the best service tomembers. Respondents are members of Primkop Kartika Ardagusema Cooperative Jl. Baros No.G-151,Cimahi. Descriptive analysis results show that Primkop Kartika Ardagusema Cooperative Savings andLoans Unit has a role in improving the welfare of members. The effort being carried out namely PrimkopKartika Ardagusema not only provides credit but also provides assistance in order to maximize the use ofcredit that has been given. The second result of the analysis the effectiveness of the credit provided byPrimkop Kartika Ardagusema Savings and Loans Unit in improving the welfare of members can be seenthat the majority of respondents stated effective. These results can be said that members of the cooperativefeel the information dissemination and transparency of cooperative products so that members canunderstand optimally related to the products offered by cooperatives.